2014
DOI: 10.1111/ggi.12363
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors associated with adverse outcome among critically ill elderly patients admitted to the intensive care unit

Abstract: Advanced age, critical illness, cardiopulmonary resuscitation, and needs for mechanical ventilation and/or vasopressor therapy are independent risk factors associated with adverse outcome in elderly patients admitted to ICU. Alternatives for ICU admission should be considered in geriatric patients with severe critical illnesses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 31 publications
4
14
0
1
Order By: Relevance
“…The need for IMV was independently associated with hospital mortality. These results are in accordance with previous findings 13,20 . Farfel et al did not consider age as a factor associated with hospital mortality in the elderly with no need for IMV 21 .…”
Section: Discussionsupporting
confidence: 94%
“…The need for IMV was independently associated with hospital mortality. These results are in accordance with previous findings 13,20 . Farfel et al did not consider age as a factor associated with hospital mortality in the elderly with no need for IMV 21 .…”
Section: Discussionsupporting
confidence: 94%
“…Several studies in developing countries have examined the clinical pattern of ICU admissions among the elderly and potential determinants of outcome including electrolyte imbalance, presence of co-morbidities, need for mechanical ventilation, sepsis and severity of illness. (10)(11)(12) However, there is paucity of data on this subject in Africa. The aim of this study was to assess the pattern and outcome of elderly admissions into the ICU of our hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical ventilation and inotropic support have been associated with mortality in patients admitted to ICU (14). In an ongoing Indian study, mechanical ventilation and inotropic support proved to increase mortality in geriatric patients (15).…”
Section: Discussionmentioning
confidence: 99%
“…In a study on 104 patients aged >85 years, van den Noortgate et al found inotropes as an independent risk factor in mortality (16). Orsini et al found that advanced age, critical illness, cardiopulmonary resuscitation, and needs for mechanical ventilation and/or vasopressor therapy are independent risk factors associated with adverse outcome in elderly patients admitted to ICU (14). Similar to these results, this investigation revealed that medical patients had higher APACHE II score, need for MV, need for inotropes, and mortality rate.…”
Section: Sim Et Al Have Found That High Simplified Acutementioning
confidence: 99%